TERAPI SABAR DENGAN TEKNIK SUFISTIK UNTUK MENINGKATKAN RESILIENSI WARGA ASRAMA AL GHOZALY PONDOK PESANTREN DARUSSALAM BLOKAGUNG BANYUWANGI - ar-rosyid, hannan; Masnida (JKaKa:Jurnal Komunikasi dan Konseling Islam, 2024)
This research discusses how to increase resilience among Al Ghozaly dormitory students who are unable to solve their problems well. This research was motivated by the large number of students who have a very low level of resilience. This research aims to: describe the forms of lack of resilience in the Al Ghozaly boarding school students at the Darussalam Islamic Boarding School Blokagung, describe the analysis of increasing the resilience of the students, describe the analysis of patient therapy using Sufistic techniques in increasing the level of resilience of the students. This research is a type of qualitative research, which produces descriptive data in the form of written words from people using a case study type. Efforts to increase resilience in students can be carried out by conducting individual counseling, firstly, with a personal approach to the client (student) which is carried out face to face between the counselor and the client. Second, providing material about the importance of resilience for students who will later be more aware and think again about the dangers posed if they are continuously haunted by feelings of anxiety and a lack of gratitude to Allah SWT. The results of the analysis show that in the implementation stage of patient therapy using Sufistic techniques is the first The counselor carries out a counseling method with a reality approach, in this counseling a personal approach is taken to the client, carried out face to face and this approach is a desire to establish closeness with the client, then provide solutions to solve the problems faced. Third, providing motivation is the same as providing coaching by providing material to clients. This coaching uses material on the importance of resilience for parents who have children with special needs and after that the final one is relaxation which aims to reduce anxiety and relax the mind so that it will be better.